Efikasi Herbisida Parakuat Diklorida Terhadap Gulma di Perkebunan Kopi Tanaman Belum Menghasilkan: Efficacy of Paraquat Dichloride Herbicide Against Weeds in Immature Coffee Plantation - Sari, Resti; Pujisiswanto, Hidayat (Gontor Agrotech Science Journal, 2024)
Testing of the control power of the paraquat dichloride herbicide in suppressing weed growth in immature coffee cultivation was carried out in Sumber Jaya, West Lampung in May-August 2023. The research aimed to obtain an effective dose of paraquat dichloride and determine its phytotoxicity to coffee plants. The treatments consisted of 5 levels of paraquat dichloride dosage, namely 276 g ha-1(B1); 414 g ha-1(B2); 552 g ha-1(B3); 690 g ha-1(B4); and 828 g ha-1(B5) and compared with manual weeding treatment (B6) and control (no treatment) (B7). The research used a Randomized Block Design (RBD) with 4 repetitions. Based on the research results, it can be seen that paraquat dichloride at a dose of 552 - 828 g ha-1 was effective in suppressing the total weed growth of the dominant weeds Asystasia gangetica, Ageratum conyzoides, Synedrella nodiflora, Ottochloa nodosa, Paspalum conjugatum, and Richardia brasiliensis until 8 days after application (DAA). Application of paraquat dichloride at a dose of 414 - 828 g ha-1 was able to control the growth of A. conyzoides and S. nodiflora weeds until 8 DAA. Application of paraquat dichloride at a dose of 276 - 828 g ha-1 on immature coffee plants did not cause symptoms of poisoning.